Strengthening Risk Management in Digital Financial Institutions (A Case Study of PT ABC) - Ratih Dewi Herawati; Tubagus M. Yusuf Khudri (E-Jurnal Akuntansi, 2025)
PT ABC, as a digital financial institution and part of the digital transformation ecosystem in the payment system, is required to implement effective risk management. This study aims to evaluate and provide recommendations for the enhancement of PT ABC’s risk management, utilizing the COSO ERM framework and the Three Lines Model. A case study approach was employed, utilizing data from employee questionnaires and internal company documents. The evaluation indicates that PT ABC’s risk management implementation covers most of the COSO ERM components but remains suboptimal, particularly in process standardization, integration of risk into strategy, and risk communication and reporting. Recommendations for strengthening PT ABC’s risk management include enhancing risk governance, defining a more specific risk appetite, developing human resource competencies, optimizing the use of measurable data, and setting risk indicators to support enterprise-wide risk management.